Pengembangan Media Pembelajaran Berbantuan Adobe Flash Berbasis Kooperatif untuk Meningkatkan Kemandirian Belajar si Siswa Kelas V UPT SD Negeri 066650 Medan Kota - Hendrikson R Panjaitan; Binnner Sihaloho (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to: 1). Describe the validity, practicality, and effectiveness of Adobe Flash-assisted learning media based on cooperative learning developed on cube and block material, 2) Describe the increase in student learning independence by using Adobe Flash-assisted learning media based on cooperative learning that has been developed. This research was conducted at SD Negeri 06650 Medan. The subjects of this study were 30 students of grade V of SD Negeri 06650 Medan in the 2021/2022 Academic Year. This research method is the Thiagarajan model development research. The results of the study showed that: 1) Adobe Flash-assisted learning media based on cooperative learning to improve students' learning independence abilities that were developed have met the criteria of valid, practical, and effective. 2) The increase in student learning independence has increased from trial I to trial II after the Adobe Flash-assisted learning media based on cooperative learning that has been developed.